Distinct associations between fronto-striatal glutamate concentrations and callous-unemotional traits and proactive aggression in disruptive behavior - Craig, Michael; Mulder, Leandra M.; Zwiers, Marcel P.; Sethi, Arjun; Hoekstra, Pieter J.; Dietrich, Andrea; Baumeister, Sarah; Aggensteiner, Pascal; Banaschewski, Tobias; Brandeis, Daniel; Werhahn, Julia E.; Walitza, Susanne; et al. (Cortex, 2019)
Disruptive behavior is associated with societally and personally problematic levels of aggression and has been linked to abnormal structure and function of fronto-amygdala-striatal regions. Abnormal glutamatergic signalling within this network may play a role in aggression. However, disruptive behavior does not represent a homogeneous construct, but can be fractionated across several dimensions. Of particular interest, callous-unemotional (CU) traits have been shown to modulate the severity, neural and behavioural characterisation, and therapeutic outcomes of disruptive behaviour disorders (DBDs) and aggression. Further, individuals showing disruptive behavior differ to the extent that they engage in subtypes of aggression (i.e., proactive [PA] and reactive aggression [RA]) which may also represent distinct therapeutic targets. Here we investigated how glutamate signalling within the fronto-amygdala-striatal circuitry was altered along these dimensions in youths showing disruptive behavior (n = 140) and typically developing controls (TD, n = 93) within the age-range of 8-18 years. We used proton magnetic resonance spectroscopy (1H-MRS) in the anterior cingulate cortex (ACC), striatum, amygdala and insula and associated glutamate concentrations with continuous measures of aggression and CU-traits using linear mixed-effects models. We found evidence of a dissociation for the different measures and glutamate concentrations. CU traits were associated with increased ACC glutamate (‘callousness’: b = .19, t (108) = 2.63, p = .01, r = .25; ‘uncaring’: b = .18, t (108) = 2.59, p = .011, r = .24) while PA was associated with decreased striatal glutamate concentration (b = −.23, t (28) = -3.02, p = .005, r = .50). These findings suggest dissociable correlates of CU traits and PA in DBDs, and indicate that the ACC and striatal glutamate may represent novel pharmacological targets in treating these different aspects.